UNDERNUTRITION PREVALENCE AMONG CHILDREN UNDER TWO YEARS OLD IN INDONESIA DURING ECONOMIC CRISIS AND ITS RELATED FACTORS - Anna Vipta Resti Mauludyani; Umi Fahmida; Otte Santika (Food and Nutrition Society of Indonesia, 2012)
The objective of this study was to assess undernutrition prevalence among children under-two years in Indonesia and its related factors. This ecological study was conducted to 437 districts using data extracted from nationally representative surveys, which were National Socioeconomic Survey (Susenas) and National Basic Health Research (Riskesdas) year 2007. Overall, prevalence of High Stunting (HS), High Wasting (HW), and High Underweight (HU) was 46.9%, 59.5%, and 17.2%, respectively. Median prevalence of inadequate intake of energy, protein, iron, and zinc were 33.3%, 11.1%, 81.8%, and 55.6%, respectively. Median prevalence of Acute Respiratory Infection (ARI) was 15.9%, while the median prevalence of diarrhea was 13.0%. Median proportion of low education of the mother was 46.9%. Prevalence of HS was associated with household income, low education proportion of mother, and proportion of food expenditure. Prevalence of HW was associated with prevalence of inadequate energy intake and proportion of food expenditure. Prevalence of HU was associated with proportion of low education of mother and proportion of food expenditure.